Dark fire - Sansom, Christofer, John 1952- (Pan Books, 2007)
In 1540, during the reign of Henry VIII, Shardlake is asked to help a young girl accused of murder. She refuses to speak in her defense even when threatened with torture. But just when the case seems lost, Thomas Cromwell, the king’s feared vicar general, offers Shardlake two more weeks to prove his client’s innocence. In exchange, Shardlake must find a lost cache of "Dark Fire," a legendary weapon of mass destruction. What ensues is a page-turning adventure, filled with period detail and history.